Empowering Parents to Improve Education : Evidence from Rural Mexico - Gertler, Paul; Patrinos, Harry; Rubio-Codina, Marta (World Bank, Washington, DC, 2012)
Mexico's compensatory education program provides extra resources to primary schools that enroll disadvantaged students in highly disadvantaged rural communities. One of the most important components of the program is the school-based management intervention known as AGEs. The impact of the AGEs is assessed on intermediate school quality indicators (failure, repetition and dropout), controlling for the presence of the conditional cash transfer program. Results prove that school-based management is an effective measure for improving outcomes, based on an over time difference-in-difference evaluation. Complementary qualitative evidence corroborates the veracity of such findings.